GAS6-based CAR-T cells exhibit potent antitumor activity against pancreatic cancer - Jiawei Fan; Ye Yu; Lanzhen Yan; Yuncang Yuan; Bin Sun; Dong Yang; Nan Liu; Jing Guo; Jie Zhang; Xudong Zhao (Journal of Hematology & Oncology, 2023)
Abstract Background The receptor tyrosine kinases TAM family (TYRO3, AXL, and MERTK) are highly expressed in multiple forms of cancer cells and tumor-associated macrophages and promote the development of cancers including pancreatic tumor. Targeting TAM receptors could be a promising therapeutic option. Methods We designed a novel CAR based on the extracellular domain of growth arrest-specific protein 6 (GAS6), a natural ligand for all TAM members. The ability of CAR-T to kill pancreatic cancer cells is tested in vitro and in vivo, and the safety is evaluated in mice and nonhuman primate. Results GAS6-CAR-T cells efficiently kill TAM-positive pancreatic cancer cell lines, gemcitabine-resistant cancer cells, and cancer stem-like cells in vitro. GAS6-CAR-T cells also significantly suppressed the growth of PANC1 xenografts and patient-derived xenografts in mice. Furthermore, these CAR-T cells did not induce obvious side effects in nonhuman primate or mice although the CAR was demonstrated to recognize mouse TAM. Conclusions Our findings indicate that GAS6-CAR-T-cell therapy may be effective for pancreatic cancers with low toxicity.